2015
DOI: 10.1590/0034-7167.2015680305i
|View full text |Cite
|
Sign up to set email alerts
|

Famílias de idosos na Estratégia de Saúde no Sul do Brasil

Abstract: the results reinforce the need to maintain a network of formal and informal support to the elderly and their families to preserve the independence or to postpone the decline in functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
1
3
0
3
Order By: Relevance
“…23 In addition, the elderly with low educational levels can suffer social exclusion and have less access to information, which are unfavorable conditions that consequently worsen the quality of life. 24 When it comes to the current occupation, pensions and government benefits are the main sources of income and support for the elderly in the Brazilian population, 25 which corroborates the results of the present study. It is emphasized that in vulnerable contexts there is a reality in which the elderly are the source of income of their family nucleus.…”
Section: Discussionsupporting
confidence: 88%
“…23 In addition, the elderly with low educational levels can suffer social exclusion and have less access to information, which are unfavorable conditions that consequently worsen the quality of life. 24 When it comes to the current occupation, pensions and government benefits are the main sources of income and support for the elderly in the Brazilian population, 25 which corroborates the results of the present study. It is emphasized that in vulnerable contexts there is a reality in which the elderly are the source of income of their family nucleus.…”
Section: Discussionsupporting
confidence: 88%
“…Similar data corroborate the findings of this work. 21,22 A study carried out with 128 older adults treated at a primary health care in a countryside municipality from the São Paulo State found that 21.4% of these older adults were vulnerable and 30.1% showed some level of frailty, according to the EFE.27 A study was carried out with 50 community older adult aiming to verify the prevalence of frailty through the EFE. The results showed that 24% of respondents were apparently vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the majority of the elderly belonged to the female gender. In fact, women have longer life expectancies, lower mortality rates due to external causes, less exposure to occupational hazards, consume less tobacco and alcohol, and seek more for social and health services when compared to men (12) . The greater prevalence of frailty in women stems from the fact that they live longer.…”
Section: Discussionmentioning
confidence: 99%